Na4Fe3 (PO4) 2 (P2O7) (at) C lithium ion battery positive electrode material, positive electrode and battery
By using Na4Fe3(PO4)2(P2O7)@C as the positive electrode material of lithium-ion battery, the problem of high production cost of the positive electrode material of lithium-ion battery is solved, high capacity, excellent rate performance and good cycle stability are achieved, and it is suitable for large-scale production.
Patent Information
- Application Number
- CN202411881678.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The high production cost of lithium-ion battery cathode materials limits its wide application in large-scale energy storage systems.
Na4Fe3(PO4)2(P2O7)@C is used as the positive electrode material of lithium-ion battery, and a carbon-coated spherical material is prepared by spray drying to reduce production costs and improve rate performance.
It achieves high capacity, excellent rate performance and excellent cycle stability, reduces the production cost of lithium-ion batteries, and is suitable for large-scale production applications.
Smart Images

Figure CN119905549A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of lithium ion batteries, and more specifically, relates to a Na4Fe3(PO4)2(P2O7)@C lithium ion battery positive electrode material, a positive electrode and a battery. Background Art
[0002] The shortage of fossil energy and environmental pollution have promoted the rapid development of renewable clean energy (such as wind energy, solar energy and tidal energy). Due to their volatility and intermittency, they cannot meet the demand for continuous and stable energy supply. Therefore, the development of economic, environmentally friendly and high-performance large-scale energy storage equipment has become the key to the development and application of renewable clean energy. Among various energy storage devices, lithium-ion batteries have demonstrated the advantages of high energy density and good long-range cycle stability. They have currently occupied a dominant position in the field of consumer electronics and are considered to be the most potential competitor for future new energy vehicles and large-scale grid energy storage systems. It is one of the most promising power sources for large-scale energy storage systems. However, limited lithium resources and rising lithium prices have severely restricted its widespread application in large-scale energy storage systems.
[0003] Positive electrode materials play a vital role in the cost and performance of lithium-ion batteries. Improving the cost-effectiveness of positive electrode materials is one of the most effective means to improve the cost-effectiveness of lithium-ion batteries. Using cheap raw materials and developing simple and economical production process routes to produce positive electrode materials is one of the most effective means to reduce the cost of lithium-ion batteries, which is conducive to the widespread application of lithium-ion batteries in large-scale energy storage systems. In traditional lithium-ion batteries, both the positive electrode material and the electrolyte are lithium-containing substances. Li, which acts as a charge carrier during the charging and discharging process, is a kind of lithium-ion battery. + The electrolyte is mainly provided by the positive electrode, and the electrolyte only serves as an ion transport medium. Since the production process of lithium-containing positive electrode materials requires the use of a large amount of lithium raw materials, the production cost of positive electrode materials is greatly increased. Lithium-containing positive electrode materials are generally framework structures with large channels for Li + Migration. The sodium homologues of some lithium-containing framework compounds are similar in structure to the lithium framework compounds. Due to the abundant reserves of sodium, the wide distribution of resources and the relatively low price, the production cost of sodium-containing framework compounds is greatly reduced. In addition, sodium and oxygen form longer Na-O bonds, which can provide a more open framework structure, so sodium-containing framework compounds generally have larger channels, which allow ions to migrate faster. If sodium-containing framework compounds with large channels are used as positive electrode materials for lithium-ion batteries, their rate performance will be greatly improved and the production cost of positive electrode materials for lithium-ion batteries will be reduced.
[0004] Transition metal elements commonly used as electrochemical redox centers are Ni, Co, Mn, Fe and V. Among them, Fe is abundant on the earth and non-toxic. Since the two metal elements Na and Fe are abundant and inexpensive, secondary battery positive electrode materials with Fe as the redox center and Na as the initial pillar and carrier of the framework structure have great advantages in cost, resources and environmental protection. In recent years, the iron-based mixed polyanion compound Na4Fe3(PO4)2(P2O7) has attracted widespread attention in the battery industry. Na4Fe3(PO4)2(P2O7) belongs to the orthorhombic crystal system, and the crystal framework is composed of [FeO6] octahedron, [PO4] tetrahedron and pyrophosphate [P2O7]. This pyrophosphate connection results in the presence of large channels in the crystal structure of Na4Fe3(PO4)2(P2O7), allowing Na + Storage and migration, thus making Na4Fe3(PO4)2(P2O7) have excellent sodium storage properties.
[0005] Due to Li + Radius Than Na + Radius Small, channels in the Na4Fe3(PO4)2(P2O7) crystal structure will be very favorable for Li + Therefore, the large channel lithium storage of Na4Fe3(PO4)2(P2O7) will give it excellent rate performance. In fact, the electrochemical behavior of de-sodiumized Na4Fe3(PO4)2(P2O7) as a lithium storage material has been reported. However, in the reported literature, before lithium storage, Na4Fe3(PO4)2(P2O7) needs to be chemically or electrochemically de-sodiumized, which is a very cumbersome step. This uneconomical production increases the manufacturing cost of lithium-ion batteries and makes it impossible to mass-produce them.
[0006] If Na4Fe3(PO4)2(P2O7) can be directly used as the positive electrode material of lithium-ion batteries, the production cost of lithium-ion batteries will be greatly reduced. Barker once used Na3V2(PO4)2F3 positive electrode and Li electrolyte to form a battery, and graphite or Li4Ti5O 12 , he found that in both cases, the negative electrode reaction is based on the lithium insertion mechanism. Barker's research shows that the Na + It will not insert into the typical negative electrode material of lithium-ion batteries, and thus will not destroy the structure of the negative electrode. Therefore, Na4Fe3(PO4)2(P2O7) will be a potential, high-rate positive electrode material for lithium-ion batteries. Therefore, the present invention urgently needs to propose a resource-rich, low-cost, high-rate Na4Fe3(PO4)2(P2O7)@C lithium-ion battery positive electrode material, positive electrode, and battery. Summary of the invention
[0011] The purpose of the present invention is to address the problem of scarce and expensive lithium resources and to propose a resource-rich, low-cost, high-rate Na4Fe3(PO4)2(P2O7)@C lithium-ion battery positive electrode material, positive electrode and battery. The present invention is the first to directly use Na4Fe3(PO4)2(P2O7)@C as a lithium-ion battery positive electrode material.
[0012] In the present invention, the applicant first directly uses Na4Fe3(PO4)2(P2O7) as the positive electrode material of the lithium-ion battery. When Na4Fe3(PO4)2(P2O7) matches the lithium electrolyte and the negative electrode material, during the first charging process, Na4Fe3(PO4)2(P2O7) undergoes electrochemical sodium removal to form NaFe3(PO4)2(P2O7). The Na removed from Na4Fe3(PO4)2(P2O7 + dissolves in the electrolyte, while Li dissociated from the lithium electrolyte + Insert the negative electrode. During the first discharge process, Li + From the negative electrode, Li in the lithium electrolyte + and a small amount of Na + It will be inserted into the NaFe3(PO4)2(P2O7) crystal framework. In the subsequent charge and discharge process, Li + and a small amount of Na + Repeatedly deintercalate at the positive electrode, while only Li is deintercalated at the negative electrode. + Since the channels in Na4Fe3(PO4)2(P2O7) can provide Na + Migration, therefore Li + and a small amount of Na + It will not destroy the crystal structure of Na4Fe3(PO4)2(P2O7).
[0013] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a Na4Fe3(PO4)2(P2O7)@C lithium-ion battery positive electrode material, wherein the Na4Fe3(PO4)2(P2O7)@C lithium-ion battery positive electrode material is prepared by dissolving an iron source compound, a phosphorus source compound, a sodium source compound, and an organic small molecule carbon source in water in sequence, spray drying the mixed solution, and sintering the solution under a protective atmosphere.
[0014] In the present invention, the Na4Fe3(PO4)2(P2O7)@C is a carbon-coated spherical material with a gray-black powder appearance.
[0015] According to the present invention, preferably, the sodium source compound is one or more of sodium hydroxide, sodium acetate, sodium chloride, sodium nitrate, sodium carbonate, sodium formate, and sodium dihydrogen phosphate.
[0016] According to the present invention, preferably, the phosphorus source compound is one or more of sodium dihydrogen phosphate, phosphoric acid, metaphosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and triammonium phosphate.
[0017] According to the present invention, preferably, the iron source compound is one or more of ferric nitrate, ferric chloride, ferric citrate and ammonium ferric citrate.
[0018] According to the present invention, preferably, the organic small molecule carbon source is one or more of glucose, sucrose, citric acid, fructose, benzoic acid, ascorbic acid and malic acid.
[0019] According to the present invention, preferably, the amount of the organic small molecule carbon source accounts for 8-30% of the mass of Na4Fe3(PO4)2(P2O7). Preferably, the organic small molecule carbon source is glucose, and the amount of glucose accounts for 10%, 15%, 20% of the mass of Na4Fe3(PO4)2(P2O7). Further, in the present invention, according to the amount of added glucose from low to high (10%, 15%, 20%), the Na4Fe3(PO4)2(P2O7)@C products are named NFPP@LC, NFPP@MC and NFPP@HC respectively.
[0020] According to the present invention, preferably, the mixed solution obtained by dissolving the iron source compound, phosphorus source compound, sodium source compound and organic small molecule carbon source in water in sequence is subjected to the spray drying treatment to obtain a powder precursor; the total concentration of sodium ions in the mixed solution is 1-2 mol / L;
[0021] The spray drying temperature is 120-180° C., the fan frequency is 30-50 Hz, and the flow rate of the mixed solution is 10-50 mL / min.
[0022] According to the present invention, preferably, the sintering temperature is 450-550°C and the sintering time is 5-15h. In the present invention, since the sintering temperature is much lower than the calcination temperature (≥700°C) of the conventional lithium-ion battery positive electrode material, the present invention greatly reduces the energy consumption in the positive electrode material production process.
[0023] According to the present invention, preferably, the protective atmosphere is a mixture of argon and hydrogen, and the hydrogen accounts for 5%-10% of the total volume of the mixture.
[0024] The second aspect of the present invention provides a positive electrode for a lithium ion battery, wherein the positive electrode for the lithium ion battery is prepared by uniformly mixing a positive electrode active material, a conductive agent and a binder to form a slurry, coating the slurry on a current collector, and drying the slurry.
[0025] The positive electrode active material is the above-mentioned Na4Fe3(PO4)2(P2O7)@C lithium ion battery positive electrode material.
[0026] According to the present invention, preferably, the mass ratio of the positive electrode active material, the conductive agent and the binder is (70-80): (10-20): (5-15).
[0027] According to the present invention, preferably, the conductive agent is at least one of acetylene black, Super P, VGCF, carbon nanotubes, carbon nanofibers, graphene and graphite.
[0028] According to the present invention, preferably, the binder is at least one of polyvinylidene fluoride, polytetrafluoroethylene and polyacrylic acid;.
[0029] According to the present invention, preferably, the drying treatment is carried out at a temperature of 95-105° C. and for a time of 10-15 h.
[0030] A third aspect of the present invention provides a lithium ion battery, wherein the positive electrode of the lithium ion battery is the positive electrode described above.
[0031] According to the present invention, preferably, the negative electrode of the lithium-ion battery is a lithium sheet.
[0032] According to the present invention, preferably, the electrolyte of the lithium-ion battery is prepared by mixing a lithium-containing compound with an organic solvent; the concentration of the lithium-containing compound in the electrolyte is 0.8-1.2M, and the lithium-containing compound is LiPF6; the organic solvent is a mixed solvent of EC and DMC, and the volume ratio of EC and DMC is (0.8-1.2):(0.8-1.2).
[0033] The beneficial effects of the technical solution of the present invention are as follows:
[0034] The present invention uses cheap Na and Fe raw materials as starting materials and adopts a simple and scalable spray drying method to synthesize Na4Fe3(PO4)2(P2O7)@C. In the present invention, carbon coating is intended to prevent the agglomeration and growth of Na4Fe3(PO4)2(P2O7) grains and improve the conductivity of Na4Fe3(PO4)2(P2O7).
[0035] The present invention is the first to directly use Na4Fe3(PO4)2(P2O7)@C as a positive electrode material for lithium-ion batteries.
[0036] In cells with lithium electrolyte and lithium metal anode, the optimized Na4Fe3(PO4)2P2O7@C exhibited high capacity (reversible capacity of 118.1 mAh g at 0.1C). -1 ), excellent rate performance (the reversible capacity at 20C is 74.9% of the reversible capacity at 0.1C) and outstanding cycle stability (the reversible capacity after 1000 cycles at 20C is 74.8 mAh g -1, with a capacity retention rate of 84.6%). Na4Fe3(PO4)2P2O7@C solves the problem that limited lithium resources and rising lithium prices have severely restricted its widespread application in large-scale energy storage systems.
[0037] Cheap raw materials, simple and economical synthesis methods, and excellent lithium storage performance indicate that Na4Fe3(PO4)2(P2O7)@C can pave the way for the production of cheap and high-rate cathode materials for lithium-ion batteries suitable for large-scale production applications.
[0038] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] The above and other objects, features and advantages of the present invention will become more apparent through a more detailed description of exemplary embodiments of the present invention in conjunction with the accompanying drawings, wherein like reference numerals generally represent like components throughout the exemplary embodiments of the present invention.
[0040] Figure 1 The preparation flow chart of a Na4Fe3(PO4)2(P2O7)@C lithium-ion battery positive electrode material provided in Example 1 of the present invention is shown (Spray solution; Spray drying; Precursor; Calcinations).
[0041] Figure 2a A scanning electron microscope image of Na4Fe3(PO4)2(P2O7)@C(NFPP@HC) obtained in Example 3 of the present invention is shown.
[0042] Figure 2b A scanning electron microscope image of Na4Fe3(PO4)2(P2O7)@C(NFPP@MC) obtained in Example 2 of the present invention is shown.
[0043] Figure 2c shows the scanning electron micrograph of Na4Fe3(PO4)2(P2O7)@C(NFPP@LC) obtained in Example 1 of the present invention and the corresponding element mapping of Na, Fe, P, O and C ( Figure 2c-1 For SEM images, Figure 2c-2 is Na mapping (EDS map), Figure 2c-3 is Fe mapping (EDS map), Figure 2c-4 is the P map (EDS map), Figure 2c-5 is O mapping (EDS map), Figure 2c-6 is C mapping (EDS map).
[0044] Figure 3The XRD patterns ("Intensity" intensity, "2θ (degree)" 2θ angle (degree)) of Na4Fe3(PO4)2(P2O7)@C obtained in Examples 1-3 of the present invention are shown.
[0045] Figure 4a The Fourier infrared spectrum (“Absorbance” absorbance, “Wavenumber” wavelength) of Na4Fe3(PO4)2(P2O7)@C(NFPP@MC) obtained in Example 2 of the present invention is shown.
[0046] Figure 4b The Fourier infrared spectra of Na4Fe3(PO4)2(P2O7)@C obtained in Examples 1-3 of the present invention are shown.
[0047] Figure 5a The first cycle CV curve diagram (“Current” current, “Potential” voltage) of Na4Fe3(PO4)2(P2O7)@C obtained in Examples 1-3 of the present invention is shown.
[0048] Figure 5b The CV curve diagram of the first 4 cycles of Na4Fe3(PO4)2(P2O7)@C(NFPP@MC) obtained in Example 2 of the present invention is shown.
[0049] Figure 5c The third cycle CV curve diagram of Na4Fe3(PO4)2(P2O7)@C obtained in Examples 1-3 of the present invention is shown. Figure 5d The first charge and discharge curves (“Voltage” voltage, “Specific Capacity” specific capacity) of Na4Fe3(PO4)2(P2O7)@C obtained in Examples 1-3 of the present invention are shown.
[0050] Figure 5e The charge and discharge curves of the first four cycles of Na4Fe3(PO4)2(P2O7)@C(NFPP@MC) obtained in Example 2 of the present invention are shown (“1st” is the first cycle, “2nd” is the second cycle, “3rd” is the third cycle, and “4th” is the fourth cycle).
[0051] Figure 5f The third cycle charge-discharge curve of Na4Fe3(PO4)2(P2O7)@C obtained in Examples 1-3 of the present invention is shown.
[0052] Figure 6aThe rate performance diagram ("Discharge Capacity" discharge capacity, "Cycle Number" cycle number) of Na4Fe3(PO4)2(P2O7)@C obtained in Examples 1-3 of the present invention is shown.
[0053] Figure 6b The charge and discharge curves of Na4Fe3(PO4)2(P2O7)@C(NFPP@MC) obtained in Example 2 of the present invention at different rates are shown.
[0054] Figure 6c The cycling performance diagram (“Coulombic efficiency”, “Current rate”, and “Charge Capacity”) of Na4Fe3(PO4)2(P2O7)@C(NFPP@MC) obtained in Example 2 of the present invention at 0.2C is shown.
[0055] Figure 6d The cycle performance diagram of Na4Fe3(PO4)2(P2O7)@C obtained in Examples 1-3 of the present invention at 5C is shown.
[0056] Figure 6e The cycle performance diagram of Na4Fe3(PO4)2(P2O7)@C obtained in Examples 1-3 of the present invention at 20C is shown.
[0057] Figure 7a The EIS graphs of Na4Fe3(PO4)2(P2O7)@C obtained in Examples 1-3 of the present invention are shown (“NFPP@LCfresh” is an uncycled NFPP@LC electrode, “NFPP@MC fresh” is an uncycled NFPP@MC electrode, “NFPP@HC fresh” is an uncycled NFPP@HC electrode, “NFPP@LC 100th” is an NFPP@LC electrode cycled for 100 cycles at 0.2C, “NFPP@MC100th” is an NFPP@MC electrode cycled for 100 cycles at 0.2C, and “NFPP@HC 100th” is an NFPP@HC electrode cycled for 100 cycles at 0.2C).
[0058] Figure 7b The R of Na4Fe3(PO4)2(P2O7)@C obtained in Examples 1-3 of the present invention based on equivalent circuit fitting is shown. ct Value(Category). DETAILED DESCRIPTION
[0059] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.
[0060] Example 1
[0061] This embodiment provides a Na4Fe3(PO4)2(P2O7)@C lithium ion battery positive electrode material. The preparation process of the Na4Fe3(PO4)2(P2O7)@C lithium ion battery positive electrode material is as follows: Figure 1 As shown, including:
[0062] 12.12g of ferric nitrate nonahydrate (Fe(NO3)3·9H2O), 6.24g of sodium dihydrogen phosphate (NaH2PO4), glucose (C6H 12 (26) was mixed with 80 mL of water to obtain a mixed solution;
[0063] spray drying the mixed solution at 160° C. to obtain a powder precursor;
[0064] The powder precursor was sintered at 500°C in an Ar / H2 (5%) atmosphere for 10 h to obtain Na4Fe3(PO4)2(P2O7)@C (gray-black powder product).
[0065] The amount of glucose used accounts for 10% of the mass of Na4Fe3(PO4)2(P2O7).
[0066] This embodiment also provides a positive electrode for a lithium-ion battery, wherein the positive electrode for the lithium-ion battery is prepared by uniformly mixing the above-mentioned Na4Fe3(PO4)2(P2O7)@C, acetylene black and polyvinylidene fluoride to form a slurry, coating the slurry on a current collector, vacuum drying at 100°C for 12h, and cutting the slurry into a disc with a radius of 6mm;
[0067] The mass ratio of the Na4Fe3(PO4)2(P2O7)@C, acetylene black and polyvinylidene fluoride is 75:15:10.
[0068] This embodiment also provides a lithium-ion battery, which is a 2032-type two-electrode button battery, wherein the positive electrode of the lithium-ion battery is the positive electrode described above;
[0069] The lithium sheet was used as the counter electrode and reference electrode;
[0070] The electrolyte was 1M LiPF6 dissolved in a 1:1 (V / V) mixed solvent of EC / DMC;
[0071] The 2032-type two-electrode button cell was assembled in an argon-filled glove box, where the water and oxygen contents were less than 10 ppm.
[0072] Example 2
[0073] The only difference between this embodiment and embodiment 1 is that the amount of glucose used accounts for 15% of the mass of Na4Fe3(PO4)2(P2O7).
[0074] Example 3
[0075] The only difference between this embodiment and embodiment 1 is that the amount of glucose used accounts for 20% of the mass of Na4Fe3(PO4)2(P2O7).
[0076] Test Example 1
[0077] This test example conducts material characterization on the Na4Fe3(PO4)2(P2O7)@C(NFPP@C) obtained in the above example.
[0078] in:
[0079] The crystal structure of NFPP@C was determined by X-ray diffractometer (XRD, ADWANCE D8, Bruker), Cu Kα radiation The tube voltage was 40 kV, the tube current was 20 mA, the 2θ angle range was 5° to 80°, and the scanning rate was 2° min -1 .
[0080] The morphology and microstructure of the samples were observed using a field emission scanning electron microscope (SEM, JEOL, JSM7500F).
[0081] The Fourier transform infrared spectra of the samples were measured using a Nicolet iG50 Fourier transform infrared spectrometer (Thermo Fisher Scientific, USA) with a wave number range of 1400–500 cm -1 .
[0082] The results are as follows:
[0083] The morphology and element distribution of the three samples of Examples 1-3 were studied by scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS). According to the SEM image of Figure 2, the three samples all showed regular spherical shapes, the diameter of the spherical particles was between 3-5 μm, the surface of the spheres was dense, and no obvious pores were observed. The EDS image of NFPP@LC is shown in Figure 2c. In the NFPP@LC microspheres, Na, Fe, O, P and C elements are evenly distributed. The uniform distribution of elements confirms that spray drying is a simple and effective method for synthesizing pure phase NFPP.
[0084] XRD patterns of NFPP@LC, NFPP@MC and NFPP@HC microspheres are shown in Figure 2. Figure 3 The XRD diffraction peaks of the three samples of Examples 1-3 are consistent with the diffraction peaks of NFPP reported previously. All three samples belong to the orthorhombic system and the Pn21a space group. The absence of any impurity diffraction peaks confirms that the three samples are highly phase pure. Figure 3 No typical diffraction peaks of crystalline carbon were observed, indicating that the pyrolysis carbon from glucose was amorphous carbon. The unit cell parameters of the three samples are shown in Table 1. It can be seen that the unit cell parameters of the three samples are similar, which are similar to the unit cell parameters of NFPP reported previously.
[0085] Table 1
[0086]
[0087] The structural characteristics of NFPP@C were further investigated by Fourier transform infrared spectroscopy (FT-IR). Figure 4a The Fourier infrared spectrum of NFPP@MC can be divided into three spectral regions. -1 The multiple absorption peaks in the range of 680-970 cm are attributed to the OPO bending vibration of the PO4 group. -1 The absorption peak is attributed to the POP stretching vibration peak of the P2O7 group. Among them, the absorption peak located in the high frequency region (954cm -1 、903cm -1 and 887cm -1 ) belongs to asymmetric stretching vibration, while the absorption peak at low frequency (737cm -1 ) belongs to symmetrical stretching vibration. Located at 970-1250cm -1 is the PO stretching vibration peak of the PO4 group. Figure 4b The Fourier transform infrared spectra of the three samples are also shown. It can be seen that the vibration spectra of the three samples are similar, indicating that the PO chemical environment of the three samples is the same.
[0088] Test Example 2
[0089] This test example performs electrochemical tests on the lithium-ion battery obtained in the above example.
[0090] The CV tests were performed on a PGSTAT 302N electrochemical workstation.
[0091] The EIS test was performed using a PGSTAT 302N electrochemical workstation with an EIS detection frequency of 100 kHz to 10 Hz.
[0092] The capacity, rate and cycle performance tests were performed using a CT2001A battery tester with a voltage range of 2.0 to 4.3 V (vs. Li / Li+ ), the battery was left to rest for 5 hours before testing.
[0093] The results are as follows:
[0094] The electrochemical behaviors of NFPP@LC, NFPP@MC, and NFPP@HC samples in LiPF6 electrolyte were investigated by CV and constant current charge-discharge tests. Li metal was used as the counter electrode and the scan rate of CV was 0.1 mV s -1 , voltage range is 2.0-4.3V (vs.Li / Li + ), the result is:
[0095] The CV graphs of the first cycle of the three samples are shown in Figure 5a Their anodic curves are similar to the CV behavior of NFPP in Na electrolyte. The two oxidation peaks at 3.30V and 3.47V indicate that sodium is released from different crystal positions. The two reduction peaks are located at 3.24V and 3.30V, respectively, and their voltage interval (0.06V) is smaller than that of NFPP in Na electrolyte, which may be due to Li + Insertion into the NFPP lattice caused. Obviously, the redox peak of NFPP@MC is the highest, indicating that this material has the fastest electrode process kinetics.
[0096] Figure 5b The CV graphs of the first four cycles of NFPP@MC are shown in Figure 1. Obviously, the CV shape of the second cycle is completely different from that of the first cycle. The voltage interval between the two oxidation peaks in the second cycle (0.05V) is much smaller than that in the first cycle (0.17V). This is mainly due to the Na + The extraction reaction converts to Li + The reduction peak at 3.24V gradually disappeared, and the position of the reduction peak at 3.30V remained unchanged. In addition, a pair of new redox peaks appeared in the low voltage region, indicating that a slight structural rearrangement of the NFPP crystal occurred. By the third cycle, the two oxidation peaks in the high voltage region merged into one oxidation peak, the reduction peak at 3.24V disappeared, and a weak reduction peak appeared at 3.1V. The CV curve of the fourth cycle overlapped with the third cycle. Figure 5b It can be seen that the anode curve of NFPP@MC changes greatly, which is mainly due to the Na + The extraction reaction converts to Li + The slight change in the cathode curve of NFPP@MC indicates that in the subsequent charge and discharge process, Na + The amount of inserted NFPP gradually decreases. In addition, the redox peak of the first cycle CV is the lowest because the first cycle positive scan is mainly Na + Out, negative sweep has some Na + Insert. Due to Na + The radius is larger and the migration rate is lower than Li +, so the redox peak of the first cycle of CV is the lowest. + The extraction / intercalation reaction gradually becomes dominant, and the entire electrode kinetics becomes faster, so the peak current gradually increases.
[0097] Figure 5c The CV graphs of the third cycle of the three samples show that the electrochemical behaviors of the three electrodes are similar, which is different from the behavior of NFPP in Na electrolyte, but similar to the behavior of NFPP after electrochemical sodium removal in Li electrolyte, indicating that the anode and cathode behaviors of the three samples in the third cycle are mainly related to Li + De- / embedding reactions.
[0098] Figure 5d It shows that the NFPP@LC, NFPP@MC and NFPP@HC cathodes have a high conductivity at 0.2C (1C = 129 mA g -1 ) rate between 2.0 and 4.3 V. The first discharge capacity of NFPP@LC and NFPP@MC is higher than the charge capacity, which may be due to the fact that some Na + This was caused by the NFPP lattice being released into the electrolyte during the 5-hour standing period.
[0099] Figure 5e The charge and discharge curves of the first four cycles of NFPP@MC are shown. It can be seen that the change trend of the charge and discharge curves of the first four cycles is similar to Figure 5b The change trend of the first four cycles of CV curves is consistent. The average voltage of the first charging process is higher than the average voltage of the following charging processes. The above CV results confirm that the first charging is mainly based on Na + The escape mechanism, and the subsequent charging is mainly based on Li + Escape mechanism. + The radius is much smaller than Na + The radius, Li + The activation barrier for the release of Na + The activation barrier of Li + The charge voltage during discharge is lower. At the same time, in the low voltage region, the first discharge voltage is lower than the subsequent discharge voltages. The above CV results confirm that during the first discharge, some Na + Inserted into the NFPP crystal frame. + The activation barrier required for insertion is high, so the discharge voltage is low. The discharge voltage and discharge capacity gradually increase in the following few times, indicating that Na + The amount of insertion gradually decreases, while Li + The amount of insertion gradually increases. + It is easier to insert / extract from the NFPP crystal frame, so the charging voltage gradually decreases and the discharge voltage gradually increases. +It is easier to insert / extract from the NFPP crystal frame, so the subsequent charge and discharge capacity gradually increases.
[0100] Figure 5f The charge-discharge curves of the third cycle of the three samples are different from those of NFPP in sodium electrolyte, but very similar to the characteristics of de-sodiumated NFPP in lithium electrolyte. The discharge capacities of NFPP@LC, NFPP@MC and NFPP@HC in the third cycle are 113.0, 114.7 and 105.0 mAh g, respectively. -1 , the coulombic efficiency of the three samples all reached 100%.
[0101] Figure 6a The rate performance diagram of the three samples at room temperature is shown. The discharge specific capacities of NFPP@MC at 0.1, 0.2, 0.5, 1, 2, 5, 10, 20, 30, and 50C are 118.1, 116.6, 114.8, 112.9, 111.6, 106.7, 101.6, 87.4, 65.7, and 27.1 mAh g -1 The discharge specific capacities of NFPP@LC and NFPP@HC at the same rate are 117.6, 115.7, 113.2, 110.2, 107.4, 102.3, 93.9, 69.8, 39.4, and 12.2 mAh g, respectively. -1 and 114.2, 106.4, 101.0, 96.5, 92.3, 85.4, 77.9, 59.5, 36.0, 10.1 mAh g -1 Obviously, all three samples showed excellent rate performance, especially NFPP@MC. It is worth noting that after cycling at ultra-high current density (50C), when the current was reduced to 0.1C, the discharge capacities of NFPP@LC, NFPP@MC, and NFPP@HC were 114.8, 117.0, and 109.8 mAh g, respectively. -1 This shows that NFPP can withstand Li + It is the charging and discharging of the carriers at high current density.
[0102] Figure 6bThe initial charge and discharge curves of NFPP@MC at 0.1, 0.2, 0.5, 1, 2, 5, 10, 20, 30, and 50C rates are shown. As the current density increases, the polarization increases and the capacity decreases. It can be seen that the capacity reduction of NFPP at high current density is caused by the increase in polarization, not structural damage, so when the current density is adjusted to a small value, the capacity of the electrode cycled at high current density will be restored. It is well known that phosphate materials are insulators with very low electronic conductivity, and the amorphous carbon generated by the pyrolysis of glucose at 500°C also has low electronic conductivity, so the overall electronic conductivity of the NFPP@C electrode synthesized in this paper is still low. If a highly conductive material such as graphene is added to the NFPP material, the polarization of NFPP will be greatly reduced, thereby further improving the rate performance of NFPP.
[0103] Figure 6c The cycling performance of NFPP@MC at 0.2C is shown. Obviously, the charge / discharge capacity gradually increases in the first few cycles. This is mainly due to the Na + The insertion / extraction amount gradually decreases, and Li + The first discharge capacity of NFPP@MC is 111.6 mAh g -1 The subsequent discharge capacity gradually increased and reached a maximum value of 116.4 mAh g at the 15th cycle. -1 After 100 cycles, the discharge capacity can be maintained at 110.9 mAh g -1 , the capacity retention rate from the first cycle to the 100th cycle is 99.4%, indicating the excellent cycling stability of NFPP@MC.
[0104] The cycling performance of the three electrodes at 5C is shown in Figure 6d As shown in Figure 2, the initial discharge specific capacities of NFPP@LC, NFPP@MC, and NFPP@HC electrodes are 102.4, 106.5, and 93.8 mAh g, respectively. -1 After 500 cycles, the discharge capacity reached 97.9, 99.0, and 73.8 mAh g -1 The capacity decay rates per cycle are 0.009%, 0.014% and 0.042% respectively.
[0105] Figure 6e The cycling performance of the three electrodes at 20C was demonstrated, and the initial discharge specific capacities of the NFPP@LC, NFPP@MC, and NFPP@HC electrodes reached 80.7, 88.4, and 55.9 mAh g, respectively. -1 After 1000 cycles, the discharge specific capacities are 52.2, 74.8, and 27.8 mAh g -1, the capacity decay rate per cycle is 0.035%, 0.015%, and 0.050%, respectively. It can be seen that the three samples still show excellent cycle stability at high current density, indicating that NFPP@C can withstand long-range charge and discharge cycles at high current density. It is worth noting that when the current density is 0.2, 5, and 20C, the specific capacity of NFPP@MC reaches the maximum value at the 15th, 21st, and 35th cycles, respectively. This is because at low current density, there are more Na + Therefore, at low current density, Na + Quickly + replace.
[0106] Figure 7a The EIS curves of the uncycled three-electrode (fresh) and the three-electrode cycled for 100 cycles at 0.2C are shown. It can be seen that all Nyquist diagrams are composed of semicircles in the high-frequency region and oblique lines in the low-frequency region. The semicircles and oblique lines are related to the charge transfer impedance and Warburg impedance, respectively. The corresponding equivalent circuit simulation diagram is shown in Figure 7a , where R s and R ct represent the electrolyte impedance and charge transfer impedance respectively, Z w represents Warburg resistance and CPE represents double-layer capacitance.
[0107] R obtained based on equivalent circuit fitting ct Value Figure 7b As shown in Figure 2, it can be seen that the charge transfer impedance of the fresh NFPP@MC electrode is the lowest (236.5Ω). Due to the formation of SEI film, the R ct Much larger than the R of the fresh electrode ct The charge transfer impedance of the three NFPP electrodes decreased significantly after 100 cycles. This is because the main charge transfer of the fresh electrodes during the EIS test is Na + , and the main migration of the electrode after 100 cycles in the EIS test is Li + , Li + The radius is smaller than Na + The radius, Li + Than Na + The migration rate is faster in the NFPP framework, so the R ct reduce. Figure 7b This indirectly indicates that the late insertion / extraction of the NFPP framework is mainly Li + This further proves that the structure of NFPP is not destroyed after long-term cycling. The charge transfer impedance of the NFPP@MC electrode after cycling is still the lowest (R ct =105.7Ω).
[0108] The present invention uses cheap Na and Fe raw materials as starting materials and adopts a simple and scalable spray drying method to successfully prepare carbon-coated NFPP@C microspheres (Na4Fe3(PO4)2(P2O7)@C). For the first time, NFPP@C is directly used as a positive electrode material for lithium-ion batteries. In a lithium battery with LiPF6 electrolyte and Li metal anode, the first anodic scanning behavior of NFPP@C is mainly based on Na + The first cathodic scan behavior is mainly based on Li + Insertion reaction. As the CV cycle proceeds, Na + The insertion / extraction reaction of Li + The insertion / extraction reaction gradually dominated, resulting in a gradual decrease in the average charge voltage and a gradual increase in the average discharge voltage in subsequent cycles. ct The value is smaller than that of the fresh NFPP@C electrode. ct Value, indicating Li + The migration speed in NFPP@C crystals is faster than that of Na + , Li + The repeated insertion / extraction of Li + The insertion / extraction reaction gradually dominated, and the electrode process kinetics became faster. Therefore, NFPP@C showed high capacity, high rate performance and excellent cycle stability as a lithium storage material. Among them, the optimized NFPP@MC can achieve a discharge capacity of 118.1 mAh g at 0.1C. -1 , and the discharge capacity can still reach 74.8 mAh g after 1000 cycles at an ultra-high rate of 20C. -1 The first reversible capacity at 20C reached 74.9% of the first reversible capacity at 0.1C. Cheap raw materials, simple production process, and excellent lithium storage performance indicate that NFPP is a very promising cathode material for lithium-ion batteries.
[0109] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.
Claims
1. A Na4Fe3(PO4)2(P2O7)@C lithium ion battery positive electrode material, characterized in that: The Na4Fe3(PO4)2(P2O7)@C lithium-ion battery positive electrode material is prepared by dissolving an iron source compound, a phosphorus source compound, a sodium source compound, and an organic small molecule carbon source in water in sequence, spray drying the mixed solution, and sintering it under a protective atmosphere.
2. The Na4Fe3(PO4)2(P2O7)@C lithium ion battery positive electrode material according to claim 1, wherein The sodium source compound is one or more of sodium hydroxide, sodium acetate, sodium chloride, sodium nitrate, sodium carbonate, sodium formate, and sodium dihydrogen phosphate; The phosphorus source compound is one or more of sodium dihydrogen phosphate, phosphoric acid, metaphosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and triammonium phosphate; The iron source compound is one or more of ferric nitrate, ferric chloride, ferric citrate, and ammonium ferric citrate; The organic small molecule carbon source is one or more of glucose, sucrose, citric acid, fructose, benzoic acid, ascorbic acid and malic acid.
3. The Na4Fe3(PO4)2(P2O7)@C lithium ion battery positive electrode material according to claim 2, wherein The organic small molecule carbon source accounts for 8-30% of the mass of Na4Fe3(PO4)2(P2O7).
4. The Na4Fe3(PO4)2(P2O7)@C lithium ion battery positive electrode material according to claim 1, wherein The mixed solution obtained by dissolving the iron source compound, phosphorus source compound, sodium source compound and organic small molecule carbon source in water in sequence is spray dried to obtain a powder precursor; the total concentration of sodium ions in the mixed solution is 1-2 mol / L; The spray drying temperature is 120-180° C., the fan frequency is 30-50 Hz, and the flow rate of the mixed solution is 10-50 mL / min.
5. The Na4Fe3(PO4)2(P2O7)@C lithium ion battery positive electrode material according to claim 1, wherein The sintering temperature is 450-550°C and the sintering time is 5-15h; The protective atmosphere is a mixed gas of argon and hydrogen, and the hydrogen accounts for 5%-10% of the total volume of the mixed gas.
6. A positive electrode for a lithium ion battery, characterized in that: The positive electrode of the lithium-ion battery is prepared by uniformly mixing a positive electrode active material, a conductive agent and a binder to form a slurry, coating the slurry on a current collector, and drying the slurry. The positive electrode active material is the Na4Fe3(PO4)2(P2O7)@C lithium ion battery positive electrode material as described in any one of claims 1-5.
7. The lithium ion battery positive electrode according to claim 6, wherein: The mass ratio of the positive electrode active material, the conductive agent and the binder is (70-80): (10-20): (5-15).
8. The lithium ion battery positive electrode according to claim 6, wherein: The conductive agent is at least one of acetylene black, Super P, VGCF, carbon nanotubes, carbon nanofibers, graphene and graphite; The binder is at least one of polyvinylidene fluoride, polytetrafluoroethylene and polyacrylic acid; The drying process is carried out at a temperature of 95-105° C. and for a time of 10-15 hours.
9. A lithium ion battery, characterized in that: The positive electrode of the lithium-ion battery is the positive electrode according to any one of claims 6 to 8.
10. The lithium ion battery according to claim 9, wherein: The negative electrode of the lithium-ion battery is a lithium sheet; The electrolyte of the lithium-ion battery is prepared by mixing a lithium-containing compound with an organic solvent; the concentration of the lithium-containing compound in the electrolyte is 0.8-1.2M, and the lithium-containing compound is LiPF6; the organic solvent is a mixed solvent of EC and DMC, and the volume ratio of EC to DMC is (0.8-1.2):(0.8-1.2).
Citation Information
Patent Citations
Mixed polyanion type sodium ion battery positive electrode material and preparation method thereof
CN116207252A
Doped modified ferric sodium pyrophosphate positive electrode material and preparation method thereof
CN116682946A
Preparation method of high-performance sodium ion battery positive electrode material Na4Fe3 (PO4) 2P2O7
CN117585658A
Positive electrode material of sodium ion battery as well as preparation method and application of positive electrode material
CN118993017A
Rechargeable Sodium Battery Containing a Solid Elastomer Electrolyte and Manufacturing Method
US20230369643A1